STRATEGI CERDAS: MANAJEMEN KEUANGAN DAN DIGITAL MARKETING UNTUK KESUKSESAN PABRIK TAHU 'DAPUR TAHU' DI LUBUK BUAYA - Sari, Laynita; Septiano, Renil; Dewi, Mike Kusuma; Zulvia, Dewi; Martha, Lidya (Jurnal Abdimas Bina Bangsa, 2025)
This community service activity aims to enhance financial management capacity and digital marketing at the "Dapur Tahu" Tofu Factory located in Lubuk Buaya, Padang City. The selection of this topic is important considering the challenges faced by the factory in maintaining market share amid intense competition and the need to leverage digital technology. The methods used include situational analysis, financial management training, and digital marketing strategies. The results obtained show an increase in employee knowledge, an increase in organic tofu product sales, and public awareness of the importance of healthy products. This activity not only provides positive impacts for the factory but also opens opportunities for further development in the future, thus contributing to local economic welfare.